Desmanchar o cinema: pesquisa com filmes Xavante no Waia Rini - Bernard Pêgo Belisário (2018)
This communicational research explores the cinematographic work of Divino Tserewahu, first indigenous filmmaker ever formed by Video in the Villages project. It accompanies his process of revisiting archive imagery and of reshooting an specific (spiritual) initiation ritual (Waia Rini) in Xavante village of Sangradouro (Brazil); and also his earlier work reviewing process that dismantle films in order to welcome new points of view, shared with the community elders but also with waradzu (non-indigenous) public. Considering this process which tears down the very idea of film as a finished work this analytical procedure takes into account not only formal or expressive filmic procedures, but also hole dynamics that surpasses it, and that come to be influenced by it. We have choose a set of documentary films shot on the last three occasions in which Waia Rini ritual was performed in Sangradouro village: Virginia Valadaos Secret of Men (1988); Divino Tserewahus Power of Dreams (2001); and Waia Rini (2015), a documentary that we made in partnership with the filmmaker during field work. On thinking and making a film together with Tserewahu it has turned to dismantle Cinema Studies research itself, taking it as part of new processes of sharing that constitute and produce Xavante cinema